ARL4C is associated with initiation and progression of lung adenocarcinoma and represents a therapeutic target. Issue 3 (22nd February 2020) - Kimura, Kenji; Matsumoto, Shinji; Harada, Takeshi; Morii, Eiichi; Nagatomo, Izumi; Shintani, Yasushi; Kikuchi, Akira
Abstract: Lung adenocarcinoma is the most common histological type of lung cancer and is classified into adenocarcinoma in situ (AIS), minimally invasive adenocarcinoma (MIA) and invasive adenocarcinoma (IA). Atypical adenomatous hyperplasia (AAH) lesions are possible precursors to adenocarcinoma. However, the mechanism underlying the stepwise continuum of lung adenocarcinoma is unclear. In this study, the involvement of ADP‐ribosylation factor (ARF)‐like (ARL) 4C (ARL4C), a member of the small GTP‐binding protein family, in the progression of lung adenocarcinoma and the possibility of ARL4C as a molecular target for lung cancer therapy were explored. ARL4C was frequently expressed in AAH and ARL4C expression in immortalized human small airway epithelial cells promoted cell proliferation and suppressed cell death. In addition, ARL4C was expressed with increased frequency in AIS, MIA and IA in a stage‐dependent manner, and the expression was correlated with histologic grade, fluorine‐18 fluorodeoxyglucose uptake and poor prognosis. An anti–sense oligonucleotide (ASO) against ARL4C (ARL4C ASO‐1316) inhibited RAS‐related C3 botulinum toxin substrate activity and nuclear import of Yes‐associated protein and transcriptional coactivator with PDZ‐binding motif, and suppressed in vitro proliferation and migration of lung cancer cells with KRAS or epidermal growth factor receptor (EGFR) mutations. In addition, transbronchial administration of ARL4C ASO‐1316 suppressed orthotopic tumor formation induced by these cancer cells. Thus, ARL4C is involved in the initiation of the premalignant stage and is associated with the stepwise continuum of lung adenocarcinoma. ARL4C ASO‐1316 would be useful for lung adenocarcinoma patients expressing ARL4C regardless of the KRAS or EGFR mutation. Abstract : ARL4C is involved in the initiation of the premalignant stage and is associated with the stepwise continuum of lung adenocarcinoma. Transbronchial administration of ARL4C ASO suppressed orthotopic tumor formation of lung cancer cells.